HEALTH EDUCATION MEMPENGARUHI PENGETAHUAN SISWA SD KELAS IV-V TENTANG MAKANAN BERGIZI SEIMBANG - Lailatul Faricha; Chilyatiz Zahroh (Universitas Nahdlatul Ulama Surabaya, 2014)
Nutritional problems are present in most class IV-V as much as approximately 35% of the students at MI Kedungturi Mufidah sub-district of Sidoarjo . Knowledge is one of the factors that affect a person's nutrition. This research aims to know the influence of health education on knowledge of students of class IV-V on a balanced nutritious food at MI Kedungturi Mufidah sub-district of Sidoarjo. This research used the pre experimental design (One-Group Pre-post-test Design). The population in this study were all the students of class IV-V MI Kedungturi Mufidah sub district of Sidoarjo, which were as many as 62 students, with the method of stratified random sampling obtained 54 respondents. The independent Variable was health education and the dependent variable was the knowledge of students. The collection of data by using a questionnaire and analyzed using the Wilcoxon Signed Rank test Test. Knowledge of students of class IV-V on a balanced nutritious diet prior to Health Education most (61,1%) of respondents have knowledge enough. Knowledge of students after health education mostly (72,2%) of respondents have good knowledge. Test results Wilcoxon Sign Rank Test suggests health education influencing students knowledge. The knowledge of students become better after health education. Health education influencing students ' knowledge about balanced nutritious meals. Influence happens is an increase in knowledge of students after being given health education regarding a balanced nutritious food. Health education is a method that can be used to increase knowledge, due to related parties (teachers and health workers) can be scheduled on these activities on a regular basis with a different topic.